Bounded Consensus Algorithms for Multi‐Agent Systems in Directed Networks. Issue 1 (8th May 2012) - Du, Haibo; Li, Shihua; Ding, Shihong
Abstract In this paper, the consensus problem is investigated via bounded controls for the multi‐agent systems with or without communication. Based on the nested saturation method, the saturated control laws are designed to solve the consensus problem. Under the designed saturated control laws, the transient performance of the closed‐loop system can be improved by tuning the saturation level. First of all, asymptotical consensus algorithms with bounded control inputs are proposed for the multi‐agent systems with or without communication delays. Under these consensus algorithms, the states' consensus can be achieved asymptotically. Then, based on a kind of novel nonlinear saturation functions, bounded finite‐time consensus algorithms are further developed. It is shown that the states' consensus can be achieved in finite time. Finally, two examples are given to verify the efficiency of the proposed methods.